PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT.COLUMBUS BAGAN BATU - Lili Afrilia; Dewita Suryati Ningsih; Ahmad Rifqi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine whether: 1. Work discipline has a significant effecton job satisfaction, 2. Work environment has a significant effect on jobsatisfaction, 3. Work discipline has a significant effect on work performance, 4.Work environment has a significant effect on job performance, 5. Job satisfactionwork work has a significant effect on work performance, 6. Work discipline has asignificant effect on job performance through job satisfaction, 7. Workenvironment has a significant effect on job performance through job satisfaction.The sampling technique used was saturated sampling technique with datacollection through observation, interviews, and questionnaire methods. Data wereobtained by distributing questionnaires related to work discipline, workenvironment, work performance and job satisfaction to 30 respondents. Dataanalysis technique in this research was partial least square using smartPLS 4application version 4.0.7.8. The results of this study indicate that 1. Workdiscipline has a significant effect on job satisfaction, 2. Work environment has asignificant effect on job satisfaction, 3. Work discipline has a significant effect onwork performance, 4. Work environment has no significant effect on workperformance, 5. Job satisfaction has an effect significant effect on workperformance, 6. Work discipline has no significant effect on achievement throughjob satisfaction, 7. Work environment has no significant effect on achievementthrough job satisfaction. Keywords: Work Discipline, Work Environment, Job Performance and JobSatisfaction